Academic performance and mental capacity of cadets engaged in sports during studies - Prontenko, K.; Hryban, Hryhorii Petrovych; Okhrimenko, I.; Bondarenko, V.; Bezpaliy, S.; Dikhtiarenko, Zoia Mykhailivna; Yeromenko, Eduard Anatoliiovych; Bulgakov, O.; Bloshchynskyi, I.; Dzenzeliuk, D. (Toluca de Lerdo, Méx., Мексика, 2019)
The article investigates the influence of sports classes on the level of study activity and mental capacity of the cadets during the study at the institution of higher military education (HMEI). 271 cadets participated in the investigation. An experimental group (EG) was formed with cadets participating in sports (n = 63) and a control group (CG) that involved cadets studying according to the traditional physical training system (n = 208). Academic performance was estimated according to the results of mastering different disciplines, mental capacity, according to the Burdon-Anfimov test. It is determined that the EG cadets had better indicators of academic performance and mental ability than the CG cadets.
Keywords: cadets; academic performance; mental capacity; studying activity; sport